Reconstructing the climatic niche breadth of land use for animal production during the African Holocene. Issue 1 (23rd October 2019) - Phelps, Leanne N.; Broennimann, Olivier; Manning, Katie; Timpson, Adrian; Jousse, Hélène; Mariethoz, Gregoire; Fordham, Damien A.; Shanahan, Timothy M.; Davis, Basil A. S.; Guisan, Antoine
Abstract: Aim: Domestic animals first appeared in the archaeological record in northern Africa c.  9000 years before present and subsequently spread southwards throughout the continent. This geographic expansion is well studied and can broadly be explained in terms of the movement of pastoralist populations due to climate change. However, no studies have explicitly evaluated changes in the climatic niche of these domesticates. A priori, one cannot assume a relationship between the geographic spread of animal production and changes in climatic niche breadth because their relationship is highly variable. Therefore, we investigated Holocene changes in the climatic niche of domestic animals (animal production) and compared these to changes in the climatic niche of hunted terrestrial ungulates. Location: The African continent. Time period: 9000–500 BP. Major taxa studied: Domestic animals, hunted (wild) terrestrial ungulates. Methods: For the first time, we applied methods from environmental niche dynamics to archaeological data to reconstruct and quantify changes in the climatic niche breadth of animal production during the African Holocene. We used faunal remains from archaeological assemblages and associated radiocarbon dates to estimate the proportion of the African climate space used for animal production and hunting at 500‐year intervals. Results: We found that the climatic niche of domestic species broadened significantly with the geographic spread, most notably during the termination of the African Humid Period, whilst no such broadening occurred for the climatic niche of hunted species. Main conclusions: Our results provide a quantitative measure of the extent to which humans have constructed and adapted the climatic niche of animal production to manage their domestic animals across increasingly diverse ecological conditions. By incorporating ecological analysis into estimations of past land use, our methods have the potential to improve reconstructions of land use change, and to provide a foundation on which further niche construction hypotheses may be tested.